2021
DOI: 10.3390/su132313099
|View full text |Cite
|
Sign up to set email alerts
|

Quality of the Wind Wave Forecast in the Black Sea Including Storm Wave Analysis

Abstract: This paper presents the results of wind wave forecasts for the Black Sea. Three different versions utilized were utilized: the WAVEWATCH III model with GFS 0.25 forcing on a regular grid, the WAVEWATCH III model with COSMO-RU07 forcing on a regular grid, and the SWAN model with COSMO-RU07 forcing on an unstructured grid. AltiKa satellite altimeter data were used to assess the quality of wind and wave forecasts for the period from 1 April to 31 December 2017. Wave height and wind speed forecast data were obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 27 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…WAVEWATCH III model is widely used for wind wave simulation in the Black Sea [e.g. [50][51][52][53]. Implementation of the wave model used in this study has shown the root mean square error RMSE = 0.25 − 0.35 m and correlation coefficient R = 0.85 − 0.9.…”
Section: Wind and Wave Reanalysis Datamentioning
confidence: 94%
See 1 more Smart Citation
“…WAVEWATCH III model is widely used for wind wave simulation in the Black Sea [e.g. [50][51][52][53]. Implementation of the wave model used in this study has shown the root mean square error RMSE = 0.25 − 0.35 m and correlation coefficient R = 0.85 − 0.9.…”
Section: Wind and Wave Reanalysis Datamentioning
confidence: 94%
“…The Utrish buoy data of this study can be regarded as a specific case because of very short distances from the coast. Attempts to assess the quality of wave models [25][26][27][28] with this data showed a deficiency of the models and the necessity of special tuning of both wind and wave blocks for the near-shore conditions. Wave modeling in inner water bodies also faces these problems [29,30].…”
Section: Of 26mentioning
confidence: 99%
“…MERRA-2 is frequently used to assess the wind resources [20,21] being estimated and in some cases could indicate much higher wind conditions compared to in situ observations [22]. For the Black Sea area, this dataset was previously used to only evaluate the performances of some wave models on a large scale [23], but it was never used to assess the wind conditions from a meteorological/renewable perspective. A direct analysis with the in situ measurements will be performed by considering two datasets, covering 4 (denoted with MERRA4) or 24 (MERRA24) values per day.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, a well-designed unstructured mesh has the same accuracy as a regular nested mesh, but it is more efficient, therefore reducing the computational time [20]. Taking advantage of the unstructured mesh, many regional wave forecasting systems have been developed, such as those for the east coast of India [22], the western Mediterranean Sea [21], and the Black Sea [23]. A high-resolution unstructured SWAN model has been implemented for the CRE recently [24].…”
Section: Introductionmentioning
confidence: 99%